2021
DOI: 10.2478/aoas-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Addition of Exogenous Fibrolytic Enzymes on Digestibility and Milk and Meat Production – A Systematic Review

Abstract: Exogenous fibrolytic enzymes (EFE) added to the ruminant diet can increase fiber digestibility and production efficiency. A systematic review was conducted to understand the interactions between EFE and diet on digestibility and animal performance. The database included variables from 384 experiments with EFE and 264 controls from 85 papers published since 2000 (classification criteria: 1) type of study (in vitro, in situ, in vivo), 2) type of ruminants (sheep, Buffaloes, goats, beef and dairy cattle), 3) prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 116 publications
1
7
0
Order By: Relevance
“…However, sometimes, adding EFEs does not have positive effects on DMD, NDFD [ 74 ] or DM intake [ 70 ]; milk production [ 13 ]; or ADG. Consistent results have been documented in meta-analyses, such as the improvement of milk production and composition; FC; and ADG [ 15 , 16 , 17 ].…”
Section: Exogenous Fibrolytic Enzymes In Ruminant Dietssupporting
confidence: 73%
See 2 more Smart Citations
“…However, sometimes, adding EFEs does not have positive effects on DMD, NDFD [ 74 ] or DM intake [ 70 ]; milk production [ 13 ]; or ADG. Consistent results have been documented in meta-analyses, such as the improvement of milk production and composition; FC; and ADG [ 15 , 16 , 17 ].…”
Section: Exogenous Fibrolytic Enzymes In Ruminant Dietssupporting
confidence: 73%
“…The use of cellulases [ 63 ], xylanases [ 64 ], ferulic acid esterases [ 65 ], and combinations of cellulase and xylanase [ 63 ] may improve the in vitro digestibility of DM (IVDMD) and IVNDFD. However, the effects of EFEs are primarily related to factors such as the cellulase-to-xylanase ratio; the type and doses of EFE; the types of ruminants, plants (legumes or grasses), or studies (in vivo, in situ, or in vitro); the ingredients of the diets; and the forage-to-concentrate ratios [ 16 , 17 , 30 , 63 ].…”
Section: Exogenous Fibrolytic Enzymes In Ruminant Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…In livestock animals, such as domestic cattle, optimal nutrition and consistent weight gain are important factors. These not only impact production efficiency, but further influence the health, longevity, and quality of products such as meat and dairy [ 15 , 16 ]. With such implications, studies on feed intake regulation and related genes are highly valuable [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the addition of EFEs can increase meat tenderness, as well as protein and essential amino acid contents (Zhou et al, 2023). Tirado-González et al (2021) applied EFE dietary supplementation and observed alterations in the fat composition of meat, notably, reduced saturated fatty acids (SFA) and increased polyunsaturated fatty acids (PUFA) contents. Nevertheless, the administra-tion of yeast and EFE as feed additives for ruminant animals is contingent on factors such as the dosage, diet composition, and method of incorporation, necessitating consideration of these aspects to achieve the goal of producing higher-quality meat (Amin and Mao, 2021).…”
Section: Introductionmentioning
confidence: 99%